Legality of State Debt Management: A Study on the Principle of the Rule of Law and Legislative Order - Nasef, M. Imam; Ali Rido; Eko Primananda (Universitas Islam Negeri Raden Intan Lampung, 2025)
The management of state receivables by the Committee of State Receivables Management (Panitia Urusan Piutang Negara), as regulated under Government Regulation No. 28 of 2022, has sparked legal debate regarding its conformity with the principle of the rule of law and legislative order. This study is motivated by concerns that the regulation unilaterally expands administrative authority, potentially infringes upon the rights of legal subjects, and undermines the principle of legality and due process of law. This research examines the validity of Government Regulation No. 28 of 2022 from the perspective of the rule of law, the hierarchy of legal norms, and the principles of proper legislative formation. This study employs a normative legal method with a statutory approach. The findings indicate that Government Regulation No. 28 of 2022 contains preambles and substantive provisions that exceed the authority granted by Law No. 49 Prp/1960 as the parent legislation, even introducing new legal norms without clear legitimacy. The study concludes that Government Regulation No. 28 of 2022 fails to comply with the principle of legality and violates the hierarchy of norms. Therefore, it should be declared invalid and subject to revocation to maintain consistency in upholding Indonesia's rule of law and legislative order.